PENGARUH UMUR PANEN TERHADAP KUALITAS MINUMAN SARI RUMPUT GANDUM (WHEATGRASS) VARIETAS GURI-3 AGRITAN - Muhammad Syafi’; Hapsari Titi Palupi (Fakultas Pertanian Universitas Yudharta Pasuruan, 2018)
This research was conducted to find out the influence of harvest age on quality of wheat grass juice varieties of guri-3 agritan. The method used is Single Randomized Block Design (RBD) with 4 treatment factors ie age 11 days, 12 days, 13 days and 14 days and 3 repetitions. Data analysis using ANOVA variance analysis with 1% and 5% confidence interval, if found influence on one variable then continued with BNT test. Observations made include Total Sugar Level, Degree of acidity (pH), yield and organoleptic test include flavor, aroma and color. The result showed that total sugar content was 3,83-6,83%, pH 6,40 - 6,53, yield 80,86% - 82,10%. There is influence of harvest age to total content of grain juice. The best treatment combination was found in U12H (12 days harvest age) with total sugar content 4,33%, pH 6,53 and yield 82,10%. The results of organoleptic tests on 20 panelists show that flavor and aroma are not accepted by the panelists while the color is still acceptable.